Struktur Retorika Karangan Narasi Mahasiswa Pendidikan Guru Sekolah Dasar STKIP PGRI Lubuklinggau - Sri Murti (Institut Agama Islam Negeri Curup, 2018)
The research aims was to describe the structure of a Narrative Essay rhetoric Describing Student primary school teacher education STKIP PGRI Lubuklinggau, using qualitative research methods. As for the steps in analyzing the following: a). data analysis will be started from an analysis of the